Comparison of [CII] 158μm line widths to luminosities - Samsonyan, A. L.
A comparison of [CII] 158μm emission line widths to different luminosities is presented to decide if any luminosity relates to velocity dispersion. [CII] 158 μm emission lines are observed with Herschel PACS for 379 galaxies and the archival data for [CII] line widths are taken from http://cassis.sirtf.com/ herschel/. Emission line widths are compared to [CII] luminosities, to near-infrared 1.6μm luminosities and to infrared 22μm luminosities. H magnitudes are taken from 2MASS catalogue, and 22μm fluxes from the WISE catalogue.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture